2018
DOI: 10.3892/ijmm.2018.3630
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1 upregulates miR-214 to promote epithelial-to-mesenchymal transition and metastasis in lung adenocarcinoma

Abstract: Epithelial-to-mesenchymal transition (EMT) is essential for the progression of non-invasive tumor cells into malignancy and metastasis. We found that miR-214 was increased in lung adenocarcinoma (LAD) and positively associated with metastasis, which was mediated by EMT. However, the mechanism whereby the overexpression of microRNAs (miRNAs), such as miR-214, promote EMT in LAD remains unclear. In this study, we found that TWIST1, an independent prognostic factor for overall survival, was increased in LAD and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(35 reference statements)
1
11
0
1
Order By: Relevance
“…These branched CDH1 + tubules in 2D cultures are more likely to represent ureteric bud derivatives and inhibiting miR-214-3p could, thus, favor ureteric bud epithelium stabilization, while restricting MM (as shown by the reduction in WT1 + cells). In agreement with this interpretation, CDH1 itself has been previously reported as a direct target of miR-214 (Wang et al, 2016), while in some cancers miR-214 was found to promote EMT (Liu et al, 2018a;Long et al, 2015;Zhao et al, 2018) and therefore inhibiting it would be expected to result in epithelial stabilization.…”
Section: Discussionsupporting
confidence: 56%
“…These branched CDH1 + tubules in 2D cultures are more likely to represent ureteric bud derivatives and inhibiting miR-214-3p could, thus, favor ureteric bud epithelium stabilization, while restricting MM (as shown by the reduction in WT1 + cells). In agreement with this interpretation, CDH1 itself has been previously reported as a direct target of miR-214 (Wang et al, 2016), while in some cancers miR-214 was found to promote EMT (Liu et al, 2018a;Long et al, 2015;Zhao et al, 2018) and therefore inhibiting it would be expected to result in epithelial stabilization.…”
Section: Discussionsupporting
confidence: 56%
“…MiR-214, a member of microRNA precursors, plays a pivotal role in the pathogenesis of multiple human disorders, including cardiovascular diseases and cancers [24,25]. The expression of miR-214 increased by TWIST1 promotes the epithelial-to-mesenchymal transition and metastasis in lung adenocarcinoma [26]. Additionally, our study portrayed that PlGF, which was highly expressed in the lung tissues of preterm rats with BPD, was negatively targeted by miR-214 and activated the STAT3 signaling pathway.…”
Section: Discussionmentioning
confidence: 69%
“…7D-E). These results lung adenocarcinoma (16). Additionally, our study portrayed that PlGF, which was highly expressed 399 in the lung tissues of preterm rats with BPD, was negatively targeted by miR-214 and activated the 400 STAT3 signaling pathway.…”
Section: Overexpression Of Mir-214 Blocks Pulmonary Angiogenesis and mentioning
confidence: 68%
“…
In recent years, the roles of microRNAs (miRNAs) in pulmonary diseases have been 16 widely studied and researched. However, the molecular mechanism by which miR-214 affects 17 bronchopulmonary dysplasia (BPD) remains elusive and merits further exploration.
…”
mentioning
confidence: 99%